New Chemical Constituent from Panax ginseng Roots - Chung, Ill-Min; Yang, Shengxiang; Kim, Seung-Hyun; Ahmad, Ateeque (Asian Journal of Chemistry, 2014)
One new constituent lanost-24-en-3b-ol-3b-D-xylopyranosyl-(2'®1'')-b-D-xylopyranoside has been isolated and identified from the methanol extract of heat processed roots of Panax ginseng. The structure of compound was elucidated with the help of 600 MHz NMR using 1D and 2D spectral methods viz., 1H and 13C aided by FAB/MS and IR spectroscopy.